Studi Potensi Lansekap Sejarah untuk Pengembangan Wisata Sejarah di Kota Singaraja - RIYANTO, SUGENG; SUKEWIJAYA, I MADE; YUSIANA, LURY SEVITA (Jurnal Arsitektur Lansekap, 2016)
ABSTRACT Study of The Potential Landscape History for The Development of Historical Tourism in Singaraja City A development of region to improve as a tourism destination will give some positive effects especially for economic sector. Singaraja city is part of northern Bali which has potential of history tourism which need to improve, that is because of the variety of history belong of there, from Buleleng Dinasty till the colonialism era in Republic of Indonesia. The improving of history tourism in Singaraja City hope will give some positive effects especially for civilians who living around. This research has done from Mei 2013 till December 2014 at administration territorial of Singaraja City. As the result of the research, over all the landscape history of Singaraja City has completed all the criteria of history tourism, although there is still need to do some treatments to develop the enchantments of the tourism destination. Based on the result of the research, it is a recommendation is a city tour system which concept learnt by travelling. Keywords: landscape, historical landscape, historical tourism